Association of brain-derived neurotrophic factor and nerve growth factor gene polymorphisms with susceptibility to migraine - Coskun, Salih; Varol, Sefer; Ozdemir, Hasan H.; Agacayak, Elif; Aydin, Birsen; Kapan, Oktay; Cevik, Mehmet Ugur (Dove Medical Press Ltd, 2016)
Migraine is one of the most common neurological diseases worldwide. Migraine pathophysiology is very complex. Genetic factors play a major role in migraine. Neurotrophic factors, such as brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF), play an important role in central nervous system functioning, development, and modulation of pain. This study investigates whether polymorphisms in the BDNF and NGF genes are associated with migraine disease in a Turkish case-control population. Overall, 576 subjects were investigated (288 patients with migraine and 288 healthy controls) for the following polymorphisms: rs6265(G/A), rs8192466(C/T), rs925946(G/T), rs2049046(A/T), and rs12273363(T/C) in the BDNF gene, and rs6330(C/T), rs11466112(C/T), rs11102930(C/A), and rs4839435(G/A) in the NGF gene using 5'-exonuclease allelic discrimination assays. We found no differences in frequency of the analyzed eight polymorphisms between migraine and control groups. However, the frequency of minor A alleles of rs6265 in BDNF gene was borderline significant in the patients compared with the healthy controls (P=0.049; odds ratios [ORs] [95% confidence intervals {CIs}] = 0.723 [0.523-0.999]). Moreover, when the migraine patients were divided into two subgroups, migraine with aura (MA) and migraine without aura (MO), the minor TT genotype of rs6330 in NGF was significantly higher in MA patients than in MO patients (P=0.036) or healthy controls (P=0.026), and this disappeared after correction for multiple testing. Also, the rs6330*T minor allele was more common in the MA group than in the MO group or controls (P=0.011, ORs [95% CIs] = 1.626 [1.117-2.365] or P=0.007, ORs [95% CIs] = 1.610 [1.140-2.274], respectively). In conclusion, this is the first clinical study to evaluate the association between BDNF and NGF polymorphisms in migraine patients compared with health controls. Our findings suggest that the NGF rs6330*T minor allele might be nominated as a risk factor for developing aura in migraine disease. Our results should be considered as preliminary, and they need to be confirmed by future studies.
Keywords: migraine; brain-derived neurotrophic factor; nerve growth factor; polymorphism; aura; migraine with aura; headache